Studies on chemical constituents of precipitation over India (MAUSAM, 1982)
The rainwater samples collected at Background Air Pollution Monitoring Network stations in India during the year 1979 are analysed for the chemical constituents of precipitation. Tables given, show the concentration of Chloride, Sulphate, Nitrate, Sodium, Potassium and Calcium. As sufficient data for monsoon period (June to September) are available total concentration of above constituents for the above period have been worked out. The mean value of ratio Chloride to Sodium concentrations for monsoon period have also been worked out. The results of analyses are discussed.